Structural analysis of bovine norovirus protruding domain - Singh, Bishal; Koromyslova, Anna D.; Hansman, Grant S. (Virology, 2016)
We determined a structure of a bovine (genogroup III, GIII) norovirus capsid protruding (P) domain using X-ray crystallography. The bovine P domain was reminiscent of other norovirus genogroups (GI, GII, GIV, and GV), but closely matched the human GI P domain. We also identified a monoclonal antibody that was capable of binding the five different (GI-GV) P domains. Our data suggests that genetically diverse noroviruses still contain common epitopes.